Mulheres que pescam ou cultivam à margem do Lago do Maicá, Santarém, Pará: aspectos socioeconômicos, ambientais e de qualidade de vida - SOUSA, Wandicleia Lopes de (Universidade Federal do Oeste do Pará, 2021)
This study approaches social, economic and environmental issues involving women who develop artisanal fishing and family farming in the Maicá and Pérola do Maicá neighborhoods in Santarém, Pará. The work has as a guiding question the following question: how is the way and the quality of life of the artisanal fisherwomen and family farmers who live in the Maicá and Pérola do Maicá neighborhoods? For answering these concerns, the objective was to understand the socioeconomic conditions and the quality of life based on the perception of the artisanal fisherwomen and family farmers having as a spatial clipping the districts of Maicá and Pérola do Maicá in Santarém. The data research were collected between March and May 2018. This is a qualitativequantitative research, and was based on a case study. The target audiences for the investigations were 11 artisanal fisherwomen and seven family farmers residing in the research neighborhoods, all members of the Z-20 Fishermen and Fishermen's Colony and the Union of Rural Workers, Farmers and Family Farmers of Santarém. The results show that the activities of family agriculture and artisanal fisheries have an essential role in food production, ensuring food and nutritional security, generating direct and indirect jobs, and helping to combat rural exodus, that is, ensuring the permanence of families in these areas. The results contribute to the recognition of women's participation in family farming, artisanal fishing activities and their performance in the local economy. In addition to, it was evident that aspects related to health, family, work, religion and community relations influence the perceptions about the quality of their lives.